SOIL SALINIZATION IN THE AGRICULTURAL AREAS OF ARMENIAN SEMI-ARID REGIONS: CASE STUDY OF MASIS REGION (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Soil salinization processes in the agricultural lands of Masis region, Armenia, were investigated. Soil samples collected from these areas at the beginning (April) and end (October) of irrigation season in 2019 were analyzed for electrical conductivity as an indication of salinity. The results of the study demonstrated that irrigation caused an intensive accumulation of soluble salts in the upper horizons of these agricultural soils posing a risk of a decline in soil productivity and of soil degradation. All of this calls for an urgent need for sustainable soil management in this region.
Keywords: groundwater quality; soil salinization; electrical conductivity; irrigation; Masis region